Biodistribution and evaluation of 131I‐labeled neuropilin‐binding peptide for targeted tumor imaging. (15th August 2016) - Dong, Ping; Cai, Huawei; Chen, Lihong; Li, Yalun; Yuan, Cen; Wu, Xiaoai; Shen, Guohua; Zhou, Huijun; Zhang, Wenjie; Li, Lin
Abstract : Neuropilin‐1 (NRP‐1) is overexpressed in several kinds of cancer cell and contributes to tumor aggressiveness. Recently, the arginine/lysine‐rich peptide with C‐terminal motifs (R/K)XX(R/K) indicated promising penetrating and transporting capability into NRP‐1 positive cancer cells. In the present study, we describe a 131 I‐labeled C‐end rule motif peptide conjugate, Tyr–tLyp‐1, for NRP‐1 positive tumor targeting and imaging properties. Briefly, a truncated Lyp‐1 peptide was designed to expose its C‐end motif and conjugated to tyrosine for radiolabeling after structural modification. The peptide indicated specific binding to A549 cancer cells at 2 μM concentration, and its binding was dependent on NRP‐1 expression and could be inhibited by other NRP‐1‐binding peptides. In vivo imaging of 131 I‐labeled Tyr–tLyp‐1peptide showed that a subcutaneous A549 xenograft tumor could be visualized using a SPECT/CT scanner. The tumor uptake of 131 I‐Tyr–tLyp‐1 was 4.77 times higher than the uptake in muscles by SPECT/CT software quantification at 6 h post injection. Together, this study indicated that truncated Lyp‐1 peptide could specifically localize in NRP‐1 positive tumors and successfully mediate the 131 I radionuclide diagnosis, indicating promising targeted imaging capability for NRP‐1 positive tumors. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : C‐end (K/R)XX(K/R) motif peptide mediates tumor imaging of 131 I‐Tyr‐tLyp‐1 to cancer cells by targeting neuropilin‐1.